165k views
3 votes
3(x + 5) − 3 = 52 − 2x

User Imee
by
5.4k points

2 Answers

4 votes
3(x+5)-3=52-2x

1.multiply inside the parentheses by 3 >> {3x+15-3=52-2x}

2. subtract 15 and 2 >>>> {3x+12=52-2x}

3. 3x-2x= 1x >>>> {x+12=52}

4. 52-12= 40 >>> {x=40}

5. answer is 40
User AntonioMO
by
5.4k points
5 votes

Answer: The value of x is 8

Explanation:

3(x + 5) − 3 = 52 − 2x

First open the bracket, and do multiplication

3x + 15 - 3 = 52 - 2x

3x + 12 = 52 -2x

Collect like terms, and make the whole expression equal to zero

3x + 12 - (52 - 2x) = 0

3x + 12 - 52 + 2x = 0

3x + 2x + 12 - 52 = 0

5x - 40 = 0

5x = 40

Divide both sides by 5

5x/5 = 40/5

x = 40/5

x = 8

User Mhabiger
by
5.4k points